Association between dietary copper, iron, zinc, selenium intake and osteopenia or osteoporosis in elderly hypertensive patients: a retrospective cohort study - Chen, Mingji; Jia, Long; Gao, Rufeng (Frontiers in Nutrition, 2024)
Aim: The study aimed to investigate the link between dietary copper, iron, zinc, selenium intake with osteopenia and osteoporosis in elderly hypertensive patients. Methods: The data of hypertensive patients were extracted from the National Health and Nutrition Examination Survey 2005-2010, 2013-2014 and 2017-2018. Data of dietary iron, zinc, copper and selenium intakes were obtained according to 24-hour diet recall interviews. Osteopenia and osteoporosis were determined based on the bone mineral density. Weighted liner regression and weighted logistic regression were employed to assess the association between iron, zinc, copper, and selenium intakes with osteopenia and osteoporosis. All results were presented as β, odds ratios (ORs), and 95% confidence intervals (CIs). Results: In total, 5,286 elderly hypertensive patients were included. Among them, 2961 (56.02%) patients have osteopenia, and 566 (10.71%) have osteoporosis. After adjusting all covariates, dietary copper intake ≥the recommended daily allowance was positively correlated with bone mineral density on total femur (β=0.086, 95%CI: 0.021-0.152) and femoral neck (β=0.097, 95%CI: 0.016-0.178). Dietary zinc intake ≥the recommended daily allowance was also positively correlated with bone mineral density on total femur (β=0.092, 95%CI: 0.030-0.153) and femoral neck (β=0.122, 95%CI: 0.050-0.193). Dietary copper (OR=0.581, 95%CI: 0.394-0.858) and zinc (OR=0.595, 95%CI: 0.429-0.827) intake ≥the recommended daily allowance levels were related to increased odds of osteoporosis in elderly with hypertension. Conclusion: Higher dietary copper and zinc intake was associated with lower odds of osteoporosis in the elderly hypertensive patients. Higher dietary intake included copper and zinc may be beneficial for the bone health in the elderly hypertensive patients.